1997
DOI: 10.1016/s0014-5793(97)00720-5
|View full text |Cite
|
Sign up to set email alerts
|

High‐affinity binding of the yeastcis‐Golgi t‐SNARE, Sed5p, to wild‐type and mutant Sly1p, a modulator of transport vesicle docking

Abstract: Docking of ER‐derived vesicles to the cis‐Golgi compartment in yeast requires vesicle and target membrane receptors (v‐SNAREs and t‐SNAREs) and the GTPase Ypt1p. The t‐SNARE Sed5p is complexed with Sly1p in vivo. The mutant form Sly1‐20p rescues Ypt1p‐lacking cells from lethality, suggesting an inhibitory function of Sly1p in v‐SNARE/t‐SNARE interaction. Using surface plasmon resonance spectroscopy, we found that Sed5p binds Sly1p and Sly1‐20p with equally high affinity (K D=5.13×10−9 M and 4.74×10−9 M, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
58
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 20 publications
9
58
0
2
Order By: Relevance
“…Munc18c was found to be phosphorylated in the basal state at multiple tyrosine residues because the individual mutation of Tyr 66 66 and Tyr 103 were not similarly tested in the context of a smaller fragment of Munc18c for the ability to confer stimulusenhanced phosphorylation, neither the Y66F nor Y103F mutation exerted a significant alteration in affinity for Syntaxin 4, suggesting against either site as crucial for Syntaxin 4 function with VAMP2 in stimulus-induced exocytosis. However, it is unclear as to why any molecules of the Munc18c-(173-255)-Y218F-EGFP mutant, which had only Tyr 219 intact, were immunoprecipitated by anti-phosphotyrosine antibody from unstimulated lysates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Munc18c was found to be phosphorylated in the basal state at multiple tyrosine residues because the individual mutation of Tyr 66 66 and Tyr 103 were not similarly tested in the context of a smaller fragment of Munc18c for the ability to confer stimulusenhanced phosphorylation, neither the Y66F nor Y103F mutation exerted a significant alteration in affinity for Syntaxin 4, suggesting against either site as crucial for Syntaxin 4 function with VAMP2 in stimulus-induced exocytosis. However, it is unclear as to why any molecules of the Munc18c-(173-255)-Y218F-EGFP mutant, which had only Tyr 219 intact, were immunoprecipitated by anti-phosphotyrosine antibody from unstimulated lysates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the dissociation of yeast homologs Sly1p (Munc18 homolog) and Sed5p (syntaxin homolog) has been shown to require the small GTPase protein Ypt1p (66). Similarly, in adipocytes, the Munc18c-Syntaxin 4 complex has been proposed to be dissociated upon activation of the Rab4 GTPase (67) or the phosphatidylinositol 3-kinase/Akt-dependent phosphorylation the of Rab GTPase-activating protein AS160 (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…The E467K mutant tentatively corresponding to yeast SLY1-20 (53) displayed mildly increased binding to syntaxin 3. The implications of this finding are, however, unclear since Grabowski and Gallwitz (54) (TI-VAMP) (47,55). We have previously shown that overexpression of Munc18-2 modifies the quantity of the other SNAREs complexed with syntaxin 3 (9).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-Sed5p antibodies were produced and purified as described previously (15). Anti-MYC (9E10) and anti-HA (12CA5) monoclonal antibodies were purchased from Santa Cruz Biotechnology, Inc., and Roche Molecular Biochemicals, respectively.…”
Section: Methodsmentioning
confidence: 99%